Retention of physicians and surgeons in rural areas—what works?. (5th March 2020) - Kumar, Shireen; Clancy, Bridget
Abstract: Background: Causes for health inequity among rural populations globally are multifactorial, and include poorer access to healthcare professionals. This study summarizes the recent literature identifying factors that influence rural doctor retention and analyses strategies implemented to increase retention. Uniquely, this study addresses the importance of context in the planning, implementation and success of these strategies, drawing on literature from high-, middle- and low-income countries. Methods: A systematic review of the English literature was conducted in two parts. The first identified factors contributing to rural doctor retention, yielding 28 studies (2015–2019). The second identified 19 studies up to 2019 that assessed the outcomes of implemented rural retention strategies. Results: Universal retention factors for health professionals in a rural environment include rural background, positive rural exposure in training or in the early postgraduate years and personal and professional support. Financial incentives were less influential on retention, but results were inconsistent between studies and differed between high-, middle- and low-income nations. Successful strategies included student selection from rural backgrounds into medical school and undergraduate education programs and early postgraduate training in a rural environment. Bundled or multifaceted interventions may be more effective than single factor interventions. Conclusion: Rural health workforce retention strategies need to be multifaceted and context specific, and cannot be effective without considering the practitioner's social context and the influence of their family in their decision making. Adequate rural health facilities, living conditions, work-life balance and family, community and professional support systems will maximize the success of implemented strategies and ensure sustainability and continuity of healthcare workforce in rural environments.